Effectiveness of E-Learning in Empowering Clinical Staffs and Health Care Employees after Meaningful Use Based on the Technology Acceptance Model - Tataei, Azadeh; Valinejadi, Ali; Seyedroghani, Panoeh; Mahdizadeh, Jamileh; Kahouei, Mehdi (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To research the attitudes of clinical and health care staff towards effectiveness of electronic learning based on the Technology Acceptance Model. Methodology: This cross-sectional study was conducted from July-September 2019. Participants in this study were staffs who had used electronic learning in-service training during six months in two health care organizations associated to Semnan University of medical sciences in Iran in 2018-2019. The census process was applied and the sampling method was not applied in the present investigation. A Persian version of the TAM questionnaire was used. Results: Participants who had adopted electronic learning were 75.8%. Mean scores of staff’s attitudes towards trend to use electronic learning was 3.61±0.77 and towards usage was 3.43±0.75. There were significant relationships among the mean scores of employees' attitudes toward the easiness of using electronic learning technology, the usage of electronic learning technology and the desire to use it (P<0.001). Conclusion: The current research reflects the practical and applied outcomes of the factors that impact on the adoption of electronic learning based on the technology acceptance model. It has been realized due to the high level of identification and attention to the factors in the infrastructure that impact on the adoption of electronic learning among staffs in health care organizations.